Biopsia de Ganglio Centinela en Cáncer de mama. Valoración en el Instituto Nacional de Oncología y Radiobiología. 2017-2019. - Martínez Carrasco, Julién; Ramos Ortiz, Mónica; Peña Torres, Keytía; Rodríguez Tamargo, Marianela; González Espinosa, Claudia; Valdés Guerrero, Orlando (Panorama. Cuba y Salud, 2021)
Objective: To evaluate the effectiveness of the Selective Sentinel Lymph Node Biopsy technique in patients with breast cancer. Methods: A retrospective-prospective descriptive study, of the case series type, was carried out in 199 patients with breast cancer admitted and operated on during the period from January 2017 to December 2019 in the Mastology Service of the National Institute of Oncology and Radiobiology. Analysis of the variables was carried out and the information was recorded in an Excel database, with which the tables were created to analyze the characteristics of the analyzed technique. Results: The age group of 51 to 60 years predominated, the most frequent location of the tumor on physical examination was in the right breast, the predominant clinical stage was IIA, and the most frequent histological type was infiltrating ductal carcinoma. The sentinel node biopsy techniques used were with dye, radiopharmaceutical and mixed, yielding an identification rate of the detected nodes of 92.5% and the highest number of identified nodes was two nodes. In addition, the surgical techniques that were used were Conservative Surgery, Modified Radical Mastectomy and others using breast reconstruction techniques. Conclusions: The Selective Sentinel Lymph Node Biopsy technique was effective in the axillary evaluation of patients with breast cancer who fulfilled the criteria for its application. Objetivo: Evaluar la efectividad de la técnica de Biopsia Selectiva del Ganglio Centinela en pacientes con Cáncer de mama. Métodos: Se realizó un estudio descriptivo retrospectivo - prospectivo, del tipo serie de casos, en 199 pacientes con cáncer de mama ingresadas e intervenidas quirúrgicamente durante el período de Enero 2017 a Diciembre 2019 en el Servicio de Mastologìa, del Instituto Nacional de Oncología y Radiobiología. Se realizó análisis de las variables y se plasmó la información en una base de datos en Excel, con la que se crearon las tablas para analizar las características de la técnica analizada. Resultados: Predominó el grupo etario de 51 a 60 años, la localización del tumor al examen físico más frecuente fue en la mama derecha, la etapa clínica predominante fue la IIA, el tipo histológico más frecuente fue el Carcinoma ductal infiltrante. Las técnicas de biopsia de Ganglio Centinela empleadas fueron con colorante, radiofármaco y mixta, arrojando una tasa de identificación de los ganglios detectados de 92,5% y el mayor número de ganglios identificados fue de dos ganglios. Además las técnicas quirúrgicas que se emplearon fueron la Cirugía Conservadora, Mastectomía Radical Modificada y otras empleando técnicas de reconstrucción mamaria. Conclusiones: La técnica de Biopsia Selectiva de Ganglio Centinela es efectiva en la evaluación axilar de las pacientes con Cáncer de mama que cumplan con los criterios de aplicación de la misma.